1996
DOI: 10.1007/bf00430412
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of chronic inflammation in retina excised after relaxing retinotomy for anterior proliferative vitreoretinopathy

Abstract: The present findings indicate that retina from eyes with advanced PVR may itself be subject to inflammatory changes, and indicate that the PVR process is not limited to retinal membranes, but involves a more widespread distribution of inflammation than is generally appreciated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
4
8
0
Order By: Relevance
“…The role of infl ammatory processes in retinas with PVR was suggested by Limb et al [31] , but their fi ndings were based only on anterior and advanced cases of PVR. In our study, the retinal tissue was obtained from the middle periphery, close to the equator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of infl ammatory processes in retinas with PVR was suggested by Limb et al [31] , but their fi ndings were based only on anterior and advanced cases of PVR. In our study, the retinal tissue was obtained from the middle periphery, close to the equator.…”
Section: Discussionmentioning
confidence: 99%
“…Limb et al [31] suggested that the retinal infl ammatory process culminated in the formation of retinal membranes. Our results suggest that retinal gliosis may also be part of the pathologic changes in PVR, at least in a signifi cant percentage of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Both, VEGF and TNF-α are not present in the retinal tissue of healthy subjects [11,12]. In human RPE cells however, VEGF expression was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline phosphatase-anti-alkaline phosphatase (APAAP) staining was performed according to previously published methods (16) as follows: Fixed slides were washed for 10 min in Trisbuffered saline pH 7.4 (0.05 M Tris in 0.15 M NaCl:TBS) and incubated for 20 min at room temperature (RT) with TBS containing 0.5% blocking reagent (Boehringer Mannheim, Germany). Cells were then incubated for 30 min at RT with 50 l/ well optimal dilutions of one of seven mouse IgG monoclonal antibodies (mAb): Bra-11, detecting CD45 (170-220 kD); KD3, detecting CD45RA (220 and 205 kDa glycoproteins); UCHL1, detecting CD45RO (180 kDa glycoprotein); PCK-26, detecting cytokeratin type 8; CY-90, detecting cytokeratin peptide 18; (Sigma Chemical Co, England); M814 detecting CD68 (Dako, UK) and RRI, detecting ICAM-1 (Boehringer Ingelheim, USA).…”
Section: Immunocytochemical (Alkaline Phosphatase-anti-alkaline Phospmentioning
confidence: 99%